TRANSFORMASI KURIKULUM PENDIDIKAN UNTUK MENINGKATKAN KOMPETENSI TEKNOLOGI DALAM ERA DIGITAL - Natasya Priyani; Nadya Revelin Putri; Atong Nazarius; Jadiaman Parhusip (LPPM Politeknik Pratama Kendal, 2024)
The advancement of information and communication technology has driven the need for curricula responsive to digital challenges. This study analyzes the implementation of Computing Curricula 2020 (CC2020) in higher education, focusing on curriculum transformation and its impact on student skills. Through document analysis, learning process observations, and graduate competency evaluations, the study found that CC2020 effectively integrates theory and practice, emphasizing technical and soft skills. Key findings include enhanced problem-solving, interdisciplinary collaboration, and adaptability to global workplaces, alongside the relevance of new programs like Artificial Intelligence and Cybersecurity. Challenges include infrastructure limitations and teacher training needs. This research contributes to the development of relevant and comprehensive IT curricula.